Can You Escape? Using Mobile App Escape Games to Create a Holistic Experiential Learning Process Online. (September 2022) - Trinh, Mai P.
Mobile app escape games are excellent tools to create an experiential learning process in online contexts. Through the act of solving puzzles to escape the rooms, students experience a process in which they need to discover new information and clues, adjust their strategies repeatedly, and become more aware of the way they learn. Their emotional and behavioral reactions when they encounter difficulties can shed light on their learning identity and learning flexibility. The experiential learning cycle is complete with the addition of after-game reflection, debrief, and discussion. Escape games are versatile and can be used to teach a variety of topics, such as problem-solving, creative thinking, teamwork, and leadership, in any kind of classroom, with any population of students. This article provides an overview of mobile app escape games, how instructors could use them in class, and examples of topics, games, and debrief questions to use.